Sincronia de floraçăo entre Lantana camara L. (Verbenaceae) e Psittacanthus calyculatus (DC.) G. Don (Loranthaceae) ocorrentes nas dunas de La Mancha, Veracruz, México. - Granja Barros, Mariluza; Rico-Gray, Victor; Díaz-Castelazo, Cecilia (Instituto de Ecología, A.C., 2001)
Lantana camara L. and Psittacanthus calyculatus (DC.) G. Don occur sympatrically and flower synchronously at La Mancha, Veracruz, Mexico. Floral strategies as morphology, colour and rewards, as well as visitors behaviour, were investigated to evaluate if floral synchrony influences pollination efficiency. L. camara is a common shrub, which occurs in clumps, flowers throughout the year, and displays showy corymbose inflorescences. P. calyculatus is a woody hemiparasite, with conspicuous inflorescences, that flowers from July to November. Both species are nectar producers, have flowers with tubular corollas, which are yellow-orange at anthesis, turning to reddish-yellow when fading. Because of their frequency and the ability to contact the sexual organs, as main (primary) pollinators of L. camara are considered the lepidopteran Agraulis vanillae, Anartia fatima, A. jatropha and Junonia sp.; whereas the hummingbirds Amazilia yucatensis and A. tzacatl, are suggested as primary pollinators of P. calyculatus. Twelve species of lepidopterans which visited flowers of both species were considered as secondary pollinators. Breeding systems tests revealed that L. camara and P. calyculatus are xenogamous and self-incompatible. Data from floral convergence, floral colour similarities and pollination syndromes suggest that these species are involved in a floral association in which both have equal benefit.